Preparation and application of liquid oxygen compatible cyanate resin suitable for dry winding
By preparing a liquid oxygen compatible cyanate resin, combined with a dry winding process, the problems of poor compatibility and insufficient low-temperature resistance in a liquid oxygen environment are solved, and high strength, low-temperature toughness and good processability are achieved, which is suitable for the manufacturing of liquid oxygen storage tanks.
Patent Information
- Application Number
- CN202411926425.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing resin-based composite materials have poor compatibility in liquid oxygen environments, insufficient low temperature resistance, and the dry winding process has problems such as high porosity and unstable molding quality.
By adjusting the material composition and ratio, a liquid oxygen compatible cyanate resin suitable for dry winding is prepared. The resin system includes cyanate resin, epoxy resin and thermoplastic resin, and non-reactive flame retardant, inorganic filler and accelerator are added to form suitable viscosity and viscosity, which is suitable for dry winding process.
The liquid oxygen compatibility and low-temperature toughness of resin-based composite materials are achieved, the tensile strength and elongation of breaking are improved, the viscosity and gel time requirements of the dry winding process are met, and the liquid oxygen storage tanks of fully composite materials are suitable for the manufacture of liquid oxygen storage tanks.
Smart Images

Figure CN119875294A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to the preparation and application of a liquid oxygen compatible cyanate ester resin suitable for dry winding. Background Art
[0002] The new generation of spacecraft has put forward higher requirements for lightweight and low-cost materials. As the largest structural section accounting for about 60% of the total weight of the spacecraft, it is urgent to carry out lightweight research on the tank. Carbon fiber composite tanks can reduce weight by about 20-40% compared with traditional metal tanks, which is one of the effective ways to achieve weight reduction of spacecraft structures.
[0003] Most polymers are prone to ignition or explosion when in contact with liquid oxygen, and have poor compatibility with liquid oxygen. When the material is in a pure liquid oxygen environment, due to the very low temperature of liquid oxygen (-183°C), the polymer chain segments do not have enough energy to move, the free volume becomes very small, and it is not possible to increase enough space for the chain segments to adjust their positions. Therefore, when subjected to external forces, the polymer chain segments are very prone to stress cracking and cracking. In addition, the thermal expansion coefficients (CTE) of the components of the composite material and the resin are quite different, and low temperature often causes microcracks and debonding at the interface between the two. At the same time, because liquid oxygen has a very strong oxidizing property, when the material is in a liquid oxygen environment and is stimulated by external forces, it is more likely to cause combustion, explosion, carbonization, etc., and the appearance of these phenomena indicates that the material is incompatible with liquid oxygen. A large number of studies and literature have shown that in order to ensure safety, the materials used to make liquid oxygen tanks must not be incompatible with liquid oxygen.
[0004] The liquid oxygen compatibility of resin-based composite materials is mainly determined by the resin matrix, so the resin matrix should be guaranteed to have good liquid oxygen compatibility. Existing research on liquid oxygen compatible resins is mainly based on epoxy resin systems, but the liquid oxygen compatibility of epoxy resin systems is generally poor, while the liquid oxygen compatibility of cyanate resins is better. However, pure cyanate resins cannot achieve complete compatibility with liquid oxygen.
[0005] The wet winding process has the disadvantages of high porosity of composite materials and difficult to control the stability of molding quality. It also has a low degree of automation, is difficult to improve production efficiency, and is not environmentally friendly. In contrast, dry winding can achieve precise control of the resin content, reduce the porosity of the composite material, and facilitate the control of product quality and improve production efficiency. However, during the dry winding process, high requirements are placed on the process properties of the resin, such as viscosity, tack, fluidity, and film-forming properties. In order to simultaneously ensure the liquid oxygen compatibility, low-temperature toughness, and prepreg processability of the resin, we successfully prepared a liquid oxygen-compatible cyanate resin suitable for dry winding by adjusting the material components and ratios. Summary of the invention
[0006] In view of this, the present invention is guided by the requirements of liquid oxygen compatibility and low-temperature toughness of all-composite liquid oxygen tanks, solves the poor compatibility of existing resin-based composite materials for preparing liquid oxygen tanks, and the limitations of insufficient low-temperature resistance and poor crack resistance of pure cyanate resins, and provides a liquid oxygen compatible cyanate resin suitable for dry winding and its preparation method and application. The resin system has excellent mechanical properties, viscosity suitable for preparing hot melt prepregs, and a long process operation window time. The prepreg produced using the resin is suitable for dry winding composite liquid oxygen tanks.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a liquid oxygen compatible cyanate ester resin suitable for dry winding, which is prepared from raw materials including the following components and parts by weight:
[0009]
[0010] The epoxy resin includes naphthalene epoxy resin and / or hydantoin epoxy resin.
[0011] The weight ratio of the cyanate resin: the epoxy resin: the thermoplastic resin is 4-5: 1-2: 0.2-1.
[0012] Preferably, the thermoplastic resin includes at least one of polysulfone, polyethersulfone, polyaryletherketone and polyetheretherketone.
[0013] Preferably, the non-reactive flame retardant includes at least one of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum hypophosphite flame retardant, tetrabromobisphenol A epoxy resin, and octaphenylsilsesquioxane.
[0014] Preferably, the inorganic filler includes at least one of gas silica, silica powder, glass beads and alumina powder.
[0015] Preferably, the accelerator includes at least one of copper acetylacetonate, cobalt acetylacetonate, cobalt isooctanoate, 2-ethyl-4-methylimidazole, and dibutyltin dilaurate.
[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned liquid oxygen compatible cyanate ester resin, comprising the following steps:
[0017] S1, melting, mixing and stirring a cyanate resin, an epoxy resin and a thermoplastic resin;
[0018] S2, cooling, adding non-reactive flame retardant and inorganic filler, stirring for a while;
[0019] S3, cooling for a second time, adding an accelerator, and stirring for a period of time to obtain the cyanate resin adhesive solution suitable for dry winding.
[0020] Preferably, in step S1, the melting temperature is 130-150°C, the stirring speed is 800-1000 rpm, and the stirring time is 3-6 hours.
[0021] In step S2, the temperature is lowered to 95-110° C.; stirring conditions: stirring speed 1000-1200 rpm; 1-2 h.
[0022] In step S3, the temperature is lowered to 85-95° C. for a second time, the stirring time is 15-30 min, and the stirring speed is 800-1000 rpm.
[0023] In a third aspect, the present invention provides the use of the above-mentioned liquid oxygen compatible cyanate ester resin in the preparation of an all-composite liquid oxygen tank.
[0024] Preferably, the application method comprises: preparing liquid oxygen compatible cyanate resin into a hot melt adhesive film, then preparing carbon fiber and the hot melt adhesive film into a prepreg, and slitting the prepreg into narrow strips, and then adopting winding molding, vacuum bag packaging and autoclave curing for molding, and the curing system is a gradient heating and pressurizing method.
[0025] In some embodiments, the preparation of the hot melt adhesive film is carried out at a temperature of 65-80°C.
[0026] In some embodiments, the preparation of the prepreg is carried out at a compounding temperature of 95-105°C.
[0027] In some embodiments, the narrow band has a size of 3-8 mm.
[0028] In some embodiments, the gradient heating and pressurizing method includes sequentially curing at 100-110°C for 1-2 hours, pressurizing to 0.5-0.7 MPa at 110-120°C and curing for 1-2 hours, and curing at 180-200°C for 3-4 hours, and the gradient heating rate is 0.5-1°C / min.
[0029] The purpose of adding cyanate resin in the present invention is to solve the viscosity, stickiness and solubility problems of the resin for hot-melt prepreg; the present invention has found in research that not all cyanate resins have excellent effects, and only bisphenol A type cyanate monomer can dissolve more epoxy resins, and obtain products with high tensile strength and elongation at break of the resin while ensuring appropriate viscosity, and can undergo prepolymerization reaction with epoxy resin to achieve a large amount of high heat-resistant triazine rings, thereby simultaneously achieving higher tensile properties and appropriate viscosity of the resin for dry winding prepreg.
[0030] Furthermore, the epoxy resin adopts naphthalene epoxy resin and / or hydantoin epoxy resin, which can improve the liquid oxygen compatibility of the system.
[0031] In the present application, the usage ratio of the cyanate resin:epoxy resin:thermoplastic resin is 4-5:1-2:0.2-1.
[0032] Only under a specific ratio can it have the ideal effect of high tensile properties, liquid oxygen impact sensitivity coefficient of 0 and 20-200Pa·s (75℃). Bisphenol A cyanate monomer improves the solubility of the system to thermoplastic resin, and epoxy resin (naphthalene epoxy resin and / or hydantoin epoxy resin) improves the liquid oxygen compatibility of the component. The synergy of the two can achieve the goal of improving the liquid oxygen compatibility and tensile properties of the resin system and keeping the resin within a suitable viscosity range.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The cyanate resin system obtained by the present invention is cured into a cast disc. According to the testing method of ASTM D2512, it can be found that there is no explosion, combustion, flash, burning or other reactions, and it is compatible with liquid oxygen.
[0035] (2) The cyanate resin system cured product prepared by the present invention has good mechanical properties, tensile strength of 80-90 MPa, tensile modulus of 3.0-4.0 GPa, and elongation at break of 3.0-3.5%, which is beneficial to improving the low temperature resistance and crack resistance of the resin at low temperatures.
[0036] (3) The cyanate resin system obtained by the present invention meets the requirements of the dry winding process for viscosity of 20-200 (Pa·s) and pot life, and the gel time at 100° C. is greater than 4 hours.
[0037] (4) The cyanate resin system obtained by the present invention can be compounded with carbon fiber to prepare prepreg, which is used to manufacture dry-wound all-composite liquid oxygen tanks. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0039] Figure 1 This is a schematic diagram of vacuum bag packaging of liquid oxygen tank by dry winding before autoclave curing;
[0040] Figure 2 It is a dry-wound storage tank after being cured in an autoclave. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0042] In each embodiment and comparative example:
[0043] Bisphenol A cyanate resin monomer: Yangzhou Tianqi New Materials Co., Ltd.
[0044] Bisphenol A cyanate resin prepolymer: Yangzhou Tianqi New Materials Co., Ltd.
[0045] Bisphenol F cyanate: Yangzhou Tianqi New Materials Co., Ltd.
[0046] Bisphenol E cyanate: Yangzhou Tianqi New Materials Co., Ltd.
[0047] Naphthalene epoxy resin: Wuhan Kemik Biopharmaceutical Technology Co., Ltd.
[0048] Hyaline Epoxy Resin: Wuhan Kemik Biopharmaceutical Technology Co., Ltd.
[0049] Glycidyl ether epoxy resin: Nan Ya Epoxy Resin (Kunshan) Co., Ltd.
[0050] Polysulfone: Guangdong Youju Advanced New Materials Co., Ltd.
[0051] Polyethersulfone: Guangdong Youju Advanced New Materials Co., Ltd.
[0052] Polyarylether copper: Zhejiang Palco New Materials Co., Ltd.
[0053] Octaphenylsilsesquioxane: Beijing Institute of Technology Flame Retardant Technology Co., Ltd.
[0054] Glass beads: Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0055] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide: Wuhan Kemik Biopharmaceutical Technology Co., Ltd. Gas silicon: Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0056] Aluminum hypophosphite flame retardant: Youfeng flame retardant
[0057] Silica powder: Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0058] Copper acetylacetonate: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0059] Cobalt acetylacetonate: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0060] Cobalt 2-ethylhexanoate: Shanghai Aladdin Biochemical Technology Co., Ltd.
[0061] Carbon fiber: Weihai Tuozhan Fiber Co., Ltd.
[0062] Example 1
[0063] The preparation steps of a liquid oxygen compatible cyanate ester resin for dry winding provided in this embodiment are as follows:
[0064] 100 parts of bisphenol A cyanate resin monomer, 20 parts of naphthalene epoxy resin, and 15 parts of polysulfone were melted at 145°C, mixed evenly and stirred for 5 hours at a stirring speed of 900 rpm;
[0065] Then the temperature was lowered to 105°C, 20 parts of octaphenylsilsesquioxane and 2 parts of glass microbeads were added, and the mixture was stirred for 1.5 h at a stirring speed of 1100 rpm;
[0066] Then the temperature was lowered to 90° C., 0.05 parts of copper acetylacetonate were added, and the mixture was stirred for 20 minutes at a stirring speed of 1000 rpm to obtain the cyanate resin suitable for dry winding.
[0067] Example 2
[0068] 100 parts of bisphenol A cyanate resin monomer, 30 parts of hydantoin epoxy resin, and 20 parts of polyethersulfone were melted at 145°C, mixed evenly, and stirred for 4 hours at a stirring speed of 900 rpm;
[0069] Then the temperature was lowered to 105°C, 10 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 2 parts of gas silicon were added, and stirred for 1.5 hours at a stirring speed of 1100 rpm;
[0070] Then the temperature was lowered to 90° C., 0.1 parts of cobalt acetylacetonate were added, and the mixture was stirred for 20 minutes at a stirring speed of 800 rpm to obtain the cyanate resin suitable for dry winding.
[0071] Example 3
[0072] 100 parts of bisphenol A cyanate resin monomer, 40 parts of hydantoin epoxy resin, and 8 parts of polyarylether copper were melted at 145°C, mixed evenly, and stirred for 3 hours at a stirring speed of 900 rpm;
[0073] Then the temperature was lowered to 105°C, 30 parts of aluminum hypophosphite flame retardant and 2 parts of silicon powder were added, and stirred for 1.5 hours at a stirring speed of 1100 rpm;
[0074] Then the temperature was lowered to 90° C., 0.2 parts of cobalt isooctanoate were added, and the mixture was stirred for 20 minutes at a stirring speed of 900 rpm to obtain the cyanate resin suitable for dry winding.
[0075] Example 4
[0076] Based on Example 1, this example provides a method for preparing an all-composite liquid oxygen tank.
[0077] First, the liquid oxygen-compatible cyanate resin prepared in Example 1 is prepared into a hot-melt adhesive film at a temperature of 70°C, and then the carbon fiber and the hot-melt adhesive film are prepared into a prepreg at a composite temperature of 95-105°C, and the prepreg is cut into 4 mm narrow strips according to usage requirements, and then formed by winding molding, vacuum bag packaging and autoclave curing. The curing system is a gradient heating and pressurizing method, which is successively cured at 100°C for 1 hour, pressurized to 0.6 MPa at 120°C and cured for 1 hour, and cured at 180°C for 4 hours, and the gradient heating rate is 0.5-1°C / min. Figure 1 This is a schematic diagram of vacuum bag packaging of liquid oxygen tank by dry winding before autoclave curing; Figure 2 The cyanate resin system obtained by the invention can be compounded with carbon fiber to prepare prepreg, which is used to manufacture dry-winding all-composite liquid oxygen tank.
[0078] Comparative Example 1
[0079] The preparation method of this comparative example is basically the same as that of Example 1, except that the bisphenol A cyanate ester monomer is replaced by bisphenol F cyanate ester.
[0080] Comparative Example 2
[0081] The preparation method of this comparative example is basically the same as that of Example 1, except that bisphenol A cyanate ester monomer is replaced by bisphenol E cyanate ester.
[0082] Comparative Example 3
[0083] The preparation method of this comparative example is basically the same as that of Example 1, except that the bisphenol A cyanate ester monomer is replaced by a bisphenol A cyanate ester prepolymer.
[0084] Comparative Example 4
[0085] The difference between this comparative example and Example 1 is that the epoxy resin adopts a glycidyl ether epoxy resin.
[0086] Comparative Example 5
[0087] The weight ratio of the cyanate resin:epoxy resin:thermoplastic resin is 6:2:1.
[0088] 120 parts of bisphenol A cyanate monomer, 40 parts of naphthalene epoxy resin, and 20 parts of polysulfone were prepared according to the preparation process of Example 1: melted at 145°C and stirred for 5h (900rpm), cooled to 105°C, 20 parts of octaphenylsilsesquioxane and 2 parts of glass beads were added, and stirred for 1.5h (1100rpm), then cooled to 90°C, 0.05 parts of copper acetylacetonate were added, and stirred for 20min (1000rpm).
[0089] Comparative Example 6
[0090] The weight ratio of the cyanate resin:epoxy resin:thermoplastic resin is 4:3:2.
[0091] 80 parts of bisphenol A cyanate monomer, 60 parts of naphthalene epoxy resin, and 40 parts of polysulfone were prepared according to the process of Example 1: mixed and stirred at 145°C for 5h (900rpm), then 20 parts of octaphenylsilsesquioxane and 2 parts of glass beads were added at 105°C and stirred for 1.5h (1100rpm), and finally 0.05 parts of copper acetylacetonate were added at 90°C and stirred for 20min (1000rpm).
[0092] Performance Testing
[0093] 1. Tensile strength test
[0094] The resin casting body was prepared according to GB / T 2567-2008 standard, and the tensile specimen was obtained after curing at 120°C × 1h + 180°C × 4h. The tensile strength, modulus and elongation at break were tested by an electronic universal material testing machine at a rate of 10 mm / min.
[0095] 2. Liquid oxygen compatibility test
[0096] The sample was prepared according to ASTM D2512G standard, and the disc sample was obtained after curing at 120°C × 1h + 180°C × 4h. The liquid oxygen compatibility was tested by a liquid oxygen impact tester.
[0097] 3. Viscosity test
[0098] The obtained resin was measured for viscosity by a rotational viscometer.
[0099] The test results of the above embodiments and comparative examples are shown in Table 1.
[0100] Table 1
[0101]
[0102] It can be seen from the data in Table 1 that the cyanate resin cured product of the present invention has excellent mechanical properties and good processability, and is suitable for dry winding process.
[0103] The cyanate resin system prepared by the present invention has a tensile strength of 80-90MPa, a tensile modulus of 3.0-4.0GPa, an elongation at break of 3.0-3.5%, and a gel time of more than 4h at 100°C. Usage: First, prepare a hot melt adhesive film and prepreg, with a coating temperature of 65-80°C and a composite temperature of 95-105°C, and cut the prepreg into narrow strips of 3.0-8.0mm according to the use requirements; then use winding molding, vacuum bag packaging and autoclave curing for molding, and the curing system is a gradient heating and pressurization method. The present invention is mainly used for the preparation of all-composite liquid oxygen storage tanks, and the preparation method is simple and the product quality is stable.
[0104] It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments may be combined with each other at will.
Claims
1. A liquid oxygen compatible cyanate resin for dry winding, characterized in that: It is prepared from the following raw materials including the following components and parts by weight: 100 parts of bisphenol A cyanate monomer; Epoxy resin 20-50 parts; 5-25 parts of thermoplastic resin; 10-30 parts of non-reactive flame retardant; 2-10 parts of inorganic filler; Accelerator 0.05-0.5 parts; The epoxy resin includes at least one of hydantoin epoxy resin and naphthalene epoxy resin.
2. The liquid oxygen compatible cyanate ester resin according to claim 1, characterized in that: The weight ratio of the cyanate resin: the epoxy resin: the thermoplastic resin is 4-5: 1-2: 0.2-1.
3. The liquid oxygen compatible cyanate ester resin according to claim 1, characterized in that: The thermoplastic resin includes at least one of polysulfone, polyethersulfone, polyaryletherketone and polyetheretherketone.
4. The liquid oxygen compatible cyanate ester resin according to claim 1, characterized in that: The non-reactive flame retardant includes at least one of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum hypophosphite flame retardant, tetrabromobisphenol A epoxy resin, and octaphenylsilsesquioxane.
5. The liquid oxygen compatible cyanate ester resin according to claim 1, characterized in that: The inorganic filler includes at least one of gas silica, silica powder, glass beads, and alumina powder; And / or, the accelerator includes at least one of copper acetylacetonate, cobalt acetylacetonate, cobalt isooctanoate, 2-ethyl-4-methylimidazole, and dibutyltin dilaurate.
6. The method for preparing a liquid oxygen compatible cyanate ester resin according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, melting, mixing and stirring a cyanate resin, an epoxy resin and a thermoplastic resin; S2, cooling, adding non-reactive flame retardant and inorganic filler, stirring for a while; S3, cooling for a second time, adding an accelerator, and stirring for a period of time to obtain the cyanate resin adhesive solution suitable for dry winding.
7. The preparation method according to claim 6, characterized in that: In step S1, the melting temperature is 130-150°C, the stirring speed is 800-1000 rpm, and the stirring time is 3-6 hours.
8. The preparation method according to claim 6, characterized in that: In step S2, the temperature is lowered to 95-110°C; stirring conditions: stirring speed 1000-1200 rpm; 1-2h.
9. The preparation method according to claim 6, characterized in that: In step S3, the temperature is lowered to 85-95° C. for a second time, the stirring time is 15-30 min, and the stirring speed is 800-1000 rpm.
10. Use of the liquid oxygen compatible cyanate ester resin according to any one of claims 1 to 5 in the preparation of an all-composite liquid oxygen tank.
Citation Information
Cited By
Shielding film and preparation method thereof
CN121319603A